THE MAIN MORPHOFUNCTIONAL CHANGES OF LIVER IN CASUAL AND SUICIDAL POISONINGS WITH ETHYLENE GLYCOL BY ACUTE AND CHRONIC STRESS - Yu. S. Kazaryan; S. I. Kolesnikov; O. N. Shashkova; V. G. Isatulin (Acta Biomedica Scientifica)
Our investigation showed that the stress-induced alteration of liver, preceding poisoning and toxic stress, accompanying poisoning and. having lingering character, intensify lesion of organ, leading to considerable injury of its parenchyma and. stroma.